2022
DOI: 10.1002/cam4.4614
|View full text |Cite
|
Sign up to set email alerts
|

Get insight into the cause of death distribution and epidemiology of penile squamous cell carcinoma: A population‐based study

Abstract: Background Penile squamous cell carcinoma (PSCC) survival had no significant improvement since 1990 in the United States. This study aims to get insight into the changing trend and distribution of death causes of PSCC. The epidemiology of PSCC is also investigated. Methods The Surveillance, Epidemiology, and End Results (SEER) (1992–2018) database is utilized to get patients diagnosed with penile squamous cell carcinoma. The trend of incidence, distribution of age, changing trend and distribution of death caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Recent studies have identified cardiovascular diseases as the primary non-cancerous cause of mortality in PC patients. As patients’ age grows, the occurrences of chronic conditions, such as diabetes, cardiac disorders, and hypertension, increase the risk of mortality ( 1 , 20 ). Notably, our findings identified tumor grade as a significant risk factor for CSS rather than OS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have identified cardiovascular diseases as the primary non-cancerous cause of mortality in PC patients. As patients’ age grows, the occurrences of chronic conditions, such as diabetes, cardiac disorders, and hypertension, increase the risk of mortality ( 1 , 20 ). Notably, our findings identified tumor grade as a significant risk factor for CSS rather than OS.…”
Section: Discussionmentioning
confidence: 99%
“…Penile cancer (PC), primarily penile squamous cell carcinoma (PSCC), is a rare malignancy that can be classified based on human papillomavirus (HPV) infection and inflammation-related etiology ( 1 , 2 ). A substantial proportion of cases are associated with HPV infection.…”
Section: Introductionmentioning
confidence: 99%
“…Penile cancer (PC) can have worse sexual or oncological outcomes with the prolonged postponement of surgery (7,8,9). This is an important point with regards to surgical approaches in the context of the COVID-19 pandemic, especially when considering the recent relatively increase of the proportion of patients who died of PC (mainly the squamous cell carcinoma) (10) and the potential diagnostic delay in the face of safety measures (11) , associated with some later recommendations for surgery during the period (invasive or obstructive cancers) (12). Ian Janes et al ( 13) even points to the potential delay in this type of diagnosis in the face of telemedicine and the lack of physical examination during the pandemic (13).…”
Section: Discussionmentioning
confidence: 99%